GAMBARAN IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI DESA BENTE WILAYAH KERJA PUSKESMAS KAMBOWA - safrin hardiansah; Rininta Andriani; Fitriani Fitriani (Kampurui Jurnal Kesehatan Masyarakat, 2023)
The low implementation PHBS in households Bente Village can be influenced by lack of understanding and lack of public awareness of PHBS program. This study aims to describe implementation of PHBS in form delivery assistance by health workers, exclusive breastfeeding, weighing infants and toddlers, using clean water, washing hands with water and soap, using healthy latrines, eradicating mosquito larvae, eating fruits and vegetables every day,  do physical activity every day, do not smoke. This type of research uses quantitative methods with a descriptive approach. Population is 116 people and sample is 116 people and sampling method is total sampling. Research data collection consisted of primary data obtained by questionnaire and secondary data obtained from records. Data processing is computerized using SPSS program. Analysis is univariate analysis, which is to see appearance of frequency distribution of each variable studied. Results obtained implementation of PHBS is 20.7%, delivery assistance health workers is 100%, exclusive breastfeeding is 62.9%, weighing infants and toddlers is 57.8%, using clean water is 100%, washing hands with water by 68.1%, using healthy latrines by 100%, eradicating mosquito larvae by 66.4%, eating fruit and vegetables every day by 67.2%, doing physical activity every day by 100%, not smoking by 39. ,7%. Conclusion shows that community in Bente Village, Kambowa Health Center Working Area, does not implement PHBS implementation. Suggestions for need for health workers to improve services for PHBS activities and need for families to increase knowledge so that they are able to carry out daily PHBS.